Efficacy and safety of brigatinib in ALK-positive non-small cell lung cancer treatment: A systematic review and meta-analysis - Xing, Puyuan; Hao, Xuezhi; Zhang, Xin; Li, Junling (Frontiers in Oncology, 2022)
Background Brigatinib is a central nervous system-active second-generation anaplastic lymphoma kinase (ALK) inhibitor that targets a broad range of ALK rearrangements in patients with non-small cell lung cancer (NSCLC). The current study aimed to analyze the pooled effects and adverse events of brigatinib in patients with ALK-positive NSCLC. Methods The pooled estimates and 95% confidence intervals (CI) were calculated with DerSimonian-Laird method and the random effect model. Results The pooled objective response rate (ORR) and disease control rate (DCR) of brigatinib were 64% (95% CI 45%-83%) and 88% (95% CI 80%-96%), respectively. The pooled mPFS was 10.52 months (95% CI 7.66-13.37). In the subgroup analyses by treatment line, the highest mPFS was reached in first-line treatment (24.00 months, 95% CI 18.40-43.20), followed by post-crizotinib second-line treatment (mPFS=16.26 months, 95% CI 12.87-19.65), and second-line with any prior ALK tyrosine kinase inhibitors (mPFS=12.96 months, 95% CI 11.14-14.78). Among patients with any baseline brain metastases, the pooled intracranial ORR (iORR) was estimated as 54% (95% CI 35%-73%) for any treatment line, and 60% (95% CI 39%-81%) for first-line treatment. Intracranial PFS (iPFS) reached 19.26 months (95% CI 14.82-23.70) in patients with any baseline brain metastases. Creatine phosphokinase (CPK) increased (44%, 95% CI 26%-63%), diarrhea (37%, 95% CI 27%-48%), and nausea (28%, 95% CI 17%-39%) of any grade were the most common adverse events. Conclusion Brigatinib is effective in the treatment of patients with ALK-positive NSCLC, particularly showing robust intracranial PFS. Brigatinib used as first-line treatment yielded superior PFS compared with brigatinib used as other treatment lines. These results suggested a benefit of using brigatinib earlier in the patient’s management. All adverse events are manageable, with CPK increased and gastrointestinal reactions found to be the most common types. Systematic Review Registration https://inplasy.com/inplasy-2022-3-0142/, identifier (INPLASY202230141).